Apoptotic cell-mediated suppression of streptococcal cell wall-induced arthritis is associated with alteration of macrophage function and local regulatory T-cell increase: a potential cell-based therapy? - Perruche, Sylvain (BioMed Central, 2009)
INTRODUCTION: Experimental streptococcal cell wall (SCW)-induced arthritis is characterized by two successive phases of the disease. The acute phase occurs early and is associated with an inflammatory process and neutrophil infiltration into the synovium. The second chronic phase is related to effector T-cell activation and the dysregulation of macrophage function. Creation of an immunomodulatory environment has been attributed to apoptotic cells themselves, apoptotic cell uptake by phagocytes as well as a less sensibility of phagocytes capturing apoptotic bodies to activation. Therefore we evaluated the potential of apoptotic cell injection to influence the course of inflammation in SCW-induced arthritis in rats. METHODS: Rat apoptotic thymocytes were injected intraperitoneally (2 × 10(8)) in addition to an arthritogenic dose of systemic SCW in LEW female rats. Control rats received SCW immunization and PBS. Rats were then followed for arthritis occurrence and circulating cytokine detection. At sacrifice, regulatory T cells (Tregs) and macrophages were analyzed. RESULTS: Apoptotic cell injection profoundly suppressed joint swelling and destruction typically observed during the acute and chronic phases of SCW-induced arthritis. Synovial inflammatory cell infiltration and bone destruction were also markedly suppressed. Ex vivo experiments revealed reduced levels of TNF in cultures of macrophages from rats challenged with SCW in the presence of apoptotic thymocytes as well as reduced macrophage response to lipopolysaccharide. Moreover, apoptotic cell injection induced higher Foxp3(+ )Tregs in the lymphoid organs, especially in the draining lymph nodes. CONCLUSIONS: Our data indicate that apoptotic cells modulate macrophage function and result in Treg generation/increase. This may be involved in inhibition of inflammation and amelioration of arthritis. This highlights and confirms previous studies showing that in vivo generation of Tregs using apoptotic cell injection may be a useful tool to prevent and treat inflammatory autoimmune responses.